Air pollution control : - Hesketh, Howard E. (Technomic Publishing Company, 1991)
This has made it extremely difficult for equipment vendors to anticipate industry requirements. Overall, the current market projections are not very favorable for the new equipment suppliers. In contrast, the service organizations are seeing increasing need for their help in areas such as dispersion modeling, troubleshooting and testing. Existing systems are being improved upon to keep them in operation. There remains a continuous need for up-to-date references and training materials to serve these needs, and it is for this purpose this revised edition is dedicated